UNMASKING A HORMONAL CHAMELEON: TSHOMA WITH HIDDEN ACTH CO-SECRETION - Nazlee, Asma’ Mohd; Chan, Pei Lin; Kuan, Yueh Chien; Tan, lorence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND TSH-secreting pituitary adenomas (TSHomas) are rare and often misdiagnosed due to overlapping features with primary thyroid disorders. Even rarer are plurihormonal pituitary adenomas that co-secrete TSH and ACTH. We report a unique case where initial evaluation suggested a TSHoma, with ACTH co-secretion only suspected perioperatively based on clinical features and was later confirmed histologically. CASE A 41-year-old woman with a two-year history of hypertension and primary infertility presented with palpitations, heat intolerance, and insomnia. She had a history of menstrual irregularities, progressing to amenorrhoea after right oophorectomy. Thyroid function tests (TFT) revealed mildly elevated FT4 (22.5 pmol/L) with normal TSH (1.37 mIU/L), prompting a diagnosis of thyrotoxicosis and treatment with carbimazole was started. Additional hormonal assessment revealed hyperprolactinemia (2138 mIU/L), hypogonadotropic hypogonadism and morning cortisol was 528 nmol/L. Pituitary MRI showed a 1.5 × 1.8 × 1.9 cm sellar-suprasellar mass compressing the optic chiasm. The discordant TFT in the presence of a sellar lesion raised suspicion for TSHoma, although SHBG was normal 41.9 nmol/L (ref: 16.8–125.2 nmol/L). She was referred for surgery. Perioperative examination revealed Cushingoid features—facial hirsutism, centripetal obesity, and dorsocervical fat pad. ACTH co-secretion was suspected. She underwent endoscopic transsphenoidal resection, during which a fungal ball was incidentally discovered in the sphenoid sinus and was managed accordingly. Postoperatively, the patient developed adrenal insufficiency with hypotension (random cortisol 24 nmol/L) requiring hydrocortisone. Histopathology confirmed a pituitary neuroendocrine tumor positive for both TSH and ACTH on immunostaining, alongside synaptophysin and chromogranin positivity, with a low Ki-67 index (1%). Postoperative thyroid and prolactin levels normalized. CONCLUSION This case highlights the diagnostic complexity of plurihormonal pituitary tumors. Although initially suspected to be a TSHoma based on discordant TFT, perioperative recognition of Cushingoid features led to the diagnosis of ACTH co-secretion confirmed via immunostaining. Careful clinical evaluation and histological confirmation are critical in such rare presentations.